Optical monitoring of systemic pathologies of the nation's health as a legal platform for a decent human life - Halkevych, Serhii (м. Чернівці, 2023)
The article is aimed at developing of a new multiparameter (statistical, correlation and fractal) laser polarimetric approach to the analysis of spatial (layered) distributions of the optical anisotropy parameters of multiple scattering biological fluids, finding of new methods of differential Mueller matrix mapping using algorithms of layered polarization-phase tomography based on differentiation of partial completely polarized and completely depolarized component of Mueller matrix to reconstruct the distributions of birefringence magnitude and linear and circular dichroism coefficients of polycrystalline networks of biological layers (polycrystalline films of plasma of donors and patients with diabetes).
Keywords: Optical monitoring, pathology, nation's health, human life